DIGITAL SMILE DESIGN - L.K. ARYKHOVA; V.V. BORISOV; A.V. SEVBITOV (Avicenna Tajik State Medical University, 2020)
Nowadays, а lot of people require the reconstruction of teeth due to their loss. Before prosthetics or any other manipulations, the person wants to see the aesthetic appearance of his future teeth as soon as possible. So far, many dentists use the verbal explanation to the patient, how a smile will look like or after the treatment the frontal row of teeth, but the visual representation of the person stays away. But now this can be achieved with the help of «Digital smile design», which shows the person the final result of the dental row. This technology has a number of advantages. Some of them are the quick creation of a prototype model and high accuracy in making the work. Due to these, technologies have facilitated communication between a specialist and a patient. Digital smile design has simplified the doctor's work process and reduced the patient's data processing time. From now on, achieving aesthetic results in the reconstruction of teeth for the dentist is not a problem.